Implementasi Pelaksanaan Pembelajaran Bagi Siswa Berkebutuhan Khusus di Kelas 1 SDN Sumbersari 1 - Nabilla Fissalma; Siti Lami'ah; Radeni Sukma Indra Dewi Lami'ah; Ratna Ekawati (Journal of Classroom Action Research, 2026)
This study aims to describe the learning process for students with special needs in Grade I at SDN Sumbersari 1 in Malang City, which functions as an inclusive school. The subjects of this study were Grade I teachers and shadow teachers. The method used in this study was a qualitative approach with a case study. Data were collected through interviews, observations, and documentation. The data analysis technique used was the data analysis components according to Braun and Clarke, which consisted of six stages, including: (1) familiarisation with the data, (2) initial coding, (3) theme construction, (4) theme re-examination, (5) theme definition and naming, and (6) writing a qualitative research report. The results showed that the learning process for students with special needs in Grade I at SDN Sumbersari 1 consisted of planning, implementation, and evaluation of learning. SDN Sumbersari 1 has an Individual Learning Programme (PPI) and Special Assistant Teachers (GPK). At the planning stage, the identification and assessment of learning modules, learning resources, and media used are the same as for regular students, but the learning process is simplified. The implementation of learning consists of an introduction, core activities, and a conclusion using approaches, methods, and media tailored to the abilities and characteristics of the students. The evaluation was conducted flexibly according to the individual abilities of the students, such as observing behaviour and coordinating intensively with parents regarding learning tasks and activities. The main challenges in inclusive learning lie in the limited time available to classroom teachers to give individual attention and the suboptimal division of roles between classroom teachers and Special Assistant Teachers (GPK) in assisting students with special needs during learning. These findings indicate a gap between the demands of inclusion policies, which are individualistic in nature, and the suboptimal division of tasks between classroom teachers and special education teachers (GPK) in the implementation of learning. The practical implications of this study are the need to strengthen school policies regarding a clear division of tasks between classroom teachers and SPAs, improve teacher training on differentiated learning strategies, and develop a more planned model of collaboration between schools and parents. These recommendations are expected to support the implementation of more effective inclusive education in primary schools.